(untitled) (Global Journal of Human-Social Science, 2023)
This paper examined the current issues and challenges facing the acquisition of OTME skills in Federal College of Education Technical Asaba Office Technology and Management is a synergy of three distinct words office technology and management It is a well-established fact that advances in technology has affected different professions with a view to meet global trends in higher productivity speed networking and excellent packaging Accomplishing the routine tasks with machines is known as automation